Bio-Based Building Materials : selected peer-reviewed full text papers from the 4th International Conference on Bio-Based Building Materials (ICBBM 2021), June 16-18, 2021, Barcelona, Spain - Amziane, Sofiane; Sonebi, Mohammed (Construction Technologies and Architecture Ser., 2022)
Selected peer-reviewed full text papers from the 4th International Conference on Bio-Based Building Materials (ICBBM 2021) Selected peer-reviewed full text papers from the 4th International Conference on Bio-Based Building Materials (ICBBM 2021), June 16-18, 2021, Barcelona, Spain.